PENGGUNAAN EKOENZIM KULIT BUAH KOPI ROBUSTA (Coffea canephora Piere) UNTUK PENGENDALIAN LARVA NYAMUK Culex sp. - Amalia, Lida; Sriwahjuningsih; Nurjannah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2023)
Mosquitoes Culex sp. become a potential vector of filariasis, so it must be controlled. One of the controls is by using ecoenzymes as natural insecticides. Coffee rind can be used as an ecoenzyme material to kill Culex sp. mosquito larvae. This research aims to find out: 1). The effect of Robusta coffee rind (Coffea canephora) ecoenzymes with various concentrations on the mortality of Culex sp mosquito larvae. 2). The most effective concentration of Robusta coffee rind (Coffea canephora) ecoenzymes on the mortality of Culex sp mosquito larvae. The method used is an experimental method with a completely randomized design (CRD), as well as 5 treatments of Robusta coffee rind ecoenzyme (0%, 5%, 10%, 15%, and 20%). The parameter observed was the mortality of Culex sp mosquito larvae for 24 hours after treatment. The data were analyzed using the Kruskal-Wallis test, because there are data that are not normally distributed. The results showed that the Robusta coffee rind (Coffea canephora) ecoenzymes affected the mortality of Culex sp mosquito larvae. The most effective ecoenzyme concentration was at a concentration of 20% with a mortality of 78% of mosquito larvae.